The potential of digital marketing in the promotion of low-density territories: the case study of Mirandela municipality - Cunha, Manuela (2021)
Information and communication technologies (ICT’S) have introduced a new form of society, the network society, with the paradigm based on digital marketing. This form of communication has constantly evolved due to its intensive study and the exponential increase in its use. The imposition of digital communication, together with social networks, becomes imperative for both organisations and territories to adjust their communication strategies in order to ensure the effectiveness of the messages conveyed. It is a very useful tool for tourist destinations marketing since it is able to materialize in itself many of the communication objectives: it stimulates the consumer’s relationship with the brand, generates buzz, attracts potential visitors, energizes the territories around an idea, encourages participation and promotes recommendation. Due to the specificity of low-density territories, digital marketing involves the consumer through instant messaging tools, facilitating the interaction between individuals, allowing the share of information (with great ease and speed) and encourage other visitors. In this work the digital presence of Mirandela (a small municipality located in the Northeast of Portugal), is analysed as well as its positioning and contents. For that purpose, data were collected in several digital channels of public and private entities. In this context and according the obtained results, it was clear that Mirandela does not prioritize the digital